Towards Inclusive Education in Tribal Areas of Odisha An Empirical Analysis - Padhi, Soubhagya Ranjan; Shanker, Deepthi; Goswami, Manash Pratim (JOURNAL OF INDIAN EDUCATION, 2021)
This paper re-examines the linkages between tribal literacy, constraints for inclusive education, and socio-economic and cultural development of the tribal society in India. Using an analytical survey of 640 households, the study empirically evaluates the factors responsible for the low literacy rates and analyses various constraints and opportunities for accessing primary education among the tribal population of Koraput district in the state of Odisha in India. The paper argues that the lack of essential infrastructure and inadequate educational incentives has significantly impacted the quality of teaching and education in the tribal schools of Koraput district. The study concludes that the successful implementation of ‘inclusive education’ in India involves revamping and restructuring the existing educational system in tribal areas, which calls for framing educational policies that are context-specific, fostering the principles of expansion, inclusion and excellence in the field of education.